2022
DOI: 10.1038/s41598-022-05107-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ligninolytic axenic and coculture white-rot fungi on rice straw chemical composition and in vitro fermentation characteristics

Abstract: The study sought to investigate the potentials of axenic cultures of Pleurotus ostreatus, Phanerochaete chrysosporium and their coculture (P. chrysosporium and P. ostreatus) to break down lignin and to enhance the rumen fermentability of rice straw. Rice straw was fermented by two lignin-degrading fungi, namely, P. ostreatus, P. chrysosporium and its coculture (P. ostreatus and P. chrysosporium) with uninoculated straw as control under solid-state fermentation employing a completely randomized research design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
2
8
0
1
Order By: Relevance
“…Many researchers have reported similar observations for straw treatment under SSF conditions. Results obtained in the present study are in agreement with the experiments conducted by Datsomor et al 70 where pretreatment of rice straw using P. ostreatus showed a marked decrease in acid detergent lignin when compared to control. The IVDMD and the total VFA concerning P .…”
Section: Resultssupporting
confidence: 93%
“…Many researchers have reported similar observations for straw treatment under SSF conditions. Results obtained in the present study are in agreement with the experiments conducted by Datsomor et al 70 where pretreatment of rice straw using P. ostreatus showed a marked decrease in acid detergent lignin when compared to control. The IVDMD and the total VFA concerning P .…”
Section: Resultssupporting
confidence: 93%
“…In this present study, it was observed that the CF, NDF, ADF and ADL were significantly (p<0.05) higher in NBCRS than the biodegraded groups. Similar observations were made by Akinfemi et al 24 , Akinfemi et al 4 , Datsomor et al 5 , Barde et al 20 . The lower values reported for the CF and the fibre fractions may be due to the hydrolytic nature of the fungi species, which could have delignified the lignocelluloses complex and utilised them by microbes during fermentation thus converting them to more useful components like protein or NFE.…”
Section: Resultssupporting
confidence: 85%
“…The possibility for turning agricultural waste into valueadded feedstuffs for ruminants with some species of white-rot fungi (Pleurotus ostreatus, Pleurotus tuber-regium, Pleurotus pulmonarius, Pleurotus sajor caju and Lentinus subnudus) have been investigated by various researchers Akinfemi et al 4 , Datsomor et al 5 . Their experiments revealed that biodegradation of agro-wastes produced significantly higher crude protein content and a significant decrease in cellulose contents.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the organic C input was mainly rice straw at all three sites, and the respective quantities of organic C input were 4.02 (argillaceous rock), 2.96 (quaternary red clay), and 2.13 t ha −1 yr −1 (granite). The lignin content of rice straw is about 10−22% (Datsomor et al., 2022; Rodríguez et al., 2008). Therefore, the more imported rice straw, the more imported lignin, the higher the exogenous C input, the higher is the recalcitrant SOC content.…”
Section: Discussionmentioning
confidence: 99%